Unique plasma metabolomic signatures of individuals with inherited disorders of long‐chain fatty acid oxidation. Issue 3 (23rd February 2016) - McCoin, Colin S.; Piccolo, Brian D.; Knotts, Trina A.; Matern, Dietrich; Vockley, Jerry; Gillingham, Melanie B.; Adams, Sean H.
Abstract: Blood and urine acylcarnitine profiles are commonly used to diagnose long‐chain fatty acid oxidation disorders (FAOD: i.e., long‐chain hydroxy‐acyl‐CoA dehydrogenase [LCHAD] and carnitine palmitoyltransferase 2 [CPT2] deficiency), but the global metabolic impact of long‐chain FAOD has not been reported. We utilized untargeted metabolomics to characterize plasma metabolites in 12 overnight‐fasted individuals with FAOD (10 LCHAD, two CPT2) and 11 healthy age‐, sex‐, and body mass index (BMI)‐matched controls, with the caveat that individuals with FAOD consume a low‐fat diet supplemented with medium‐chain triglycerides (MCT) while matched controls consume a typical American diet. In plasma 832 metabolites were identified, and partial least squared‐discriminant analysis (PLS‐DA) identified 114 non‐acylcarnitine variables that discriminated FAOD subjects and controls. FAOD individuals had significantly higher triglycerides and lower specific phosphatidylethanolamines, ceramides, and sphingomyelins. Differences in phosphatidylcholines were also found but the directionality differed by metabolite species. Further, there were few differences in non‐lipid metabolites, indicating the metabolic impact of FAOD specifically on lipid pathways. This analysis provides evidence that LCHAD/CPT2 deficiency significantly alters complex lipid pathway flux. This metabolic signature may provide new clinical tools capable of confirming or diagnosing FAOD, even in subjects with a mild phenotype, and may provide clues regarding the biochemical and metabolic impact of FAOD that is relevant to the etiology of FAOD symptoms.